Political uncertainty and firm performance: Does Shariah compliance matter? - Abdelaal, Nourhan (AUC Knowledge Fountain, 2020)
The purpose of this thesis is to investigate the relationship between political uncertainty and the performance of Shariah compliant firms. This thesis will examine the relationship between political instability and the performance of Shariah compliant versus non-Shariah complaint firms. This relationship will be examined on two samples. The first sample includes panel data of 12 emerged countries and 6 emerging countries, while the second sample covers US data. Two measures of political instability will be used. The first one is the International Country Risk Guide (ICRG) Index and the second one is elections period. Two OLS models are implemented; both models provide evidence that Shariah compliance has a positive significant effect on firms' performance. The panel data provide evidence that Shariah compliant firms perform better during periods of political instability. However, presidential elections negatively affect performance of Shariah complaint firms in the US.